The Transformation of Heritage Tourism Marketing through TikTok A Study of Gen Z’s Interest in Surabaya’s Old Town - Mochammad Arkansyah; Anita Agustina Wulandari; Yuga Adi Kusuma; Arfiyansyah (LPPM Stikosa - AWS, 2025)
This study aims to describe how the transformation of heritage tourism marketing strategies is carried out through the TikTok platform, and how it influences the travel interest of Generation Z visitors to the Kota Tua Surabaya destination. Using a descriptive qualitative approach, this research observes TikTok content promoting Kota Tua Surabaya, conducts interviews with content creators and local tourism stakeholders, and gathers insights from Gen Z TikTok users through in-depth interviews. The findings indicate that TikTok, as a short-video-based social media platform, provides strong visual and emotional appeal, particularly through the use of trending music, storytelling narratives, and cinematic visuals. Authentic, interactive, and relatable content has proven to be more effective in increasing awareness and interest among Gen Z. The transformation of heritage tourism marketing through TikTok not only expands promotional reach but also helps shape a modern and digitally relevant image of the destination.